PENTINGNYA POLA KEMITRAAN DALAM RANGKA MENINGKATKAN PERAN DAN KINERJA USAHA MIKRO, KECIL, DAN MENENGAH DI JAWA TIMUR PERIODE 2006 – 2011 - Wanda Marsa Widyani (Perpustakaan Universitas Surabaya, 2014)
Micro, Small and Medium Enterprises has a large role in the economy of the people in East Java , and UMKM development efforts in East Java has been done , either by the central government , provincial, district , city , state , and local enterprises . Problems faced by UMKM is still structurally encompasses so many UMKM are actually feasible but not bankable . To overcome these problems, one of the efforts that can be done is through